Organisation Commitment and Turnover Intention of Employees in Saudi Arabia - Alharbi, Elham (2022)
Due to the importance of obtaining and maintaining employee’s commitment, this study aimed to assess the impact of intrinsic, social, and extrinsic rewards on three components of organisational commitment (affective, normative and continuance) and turnover intention for employees in Saudi Arabia. Data for this study were collected using an online survey of 227 employees in Saudi Arabia. The results of this study demonstrate the importance of intrinsic, social, and extrinsic rewards for the enhancement of affective and normative organisational commitment and turnover intention for employees in Saudi Arabia. However, the results do not show any correlation between the reward suggestion and continuance commitment. The results indicate associations between skill variety, training and career development, supervisor support, pay satisfaction and affective and normative organisational commitment, while task significance was correlated with affective organisational commitment. Turnover intention was associated with intrinsic rewards (autonomy and skill variety, training and career development), and social rewards (supervisor support) and extrinsic rewards (pay satisfaction). This research provides insight into how employees in Saudi Arabia reciprocate the perceived rewards provided by their organisations to obtain employee commitment and to mitigate their intention to leave. Additionally, the study provides a new perspective on the Saudi human resource management context, which is useful for elucidating what kinds of rewards encourage Saudi employees’ organisational commitment and desire to stay with an organisation. In addition, this research contributes to the empirical evidence of intrinsic, social, and extrinsic rewards; organisational commitment; turnover intention and exchange theory.